Case reportMelkersson-Rosenthal syndrome misdiagnosed as recurrent Quincke’s oedema - Arkuszewska, Cecylia; Słowik-Rylska, Małgorzata; Sysa-Jędrzejowska, Anna; Lesiak, Aleksandra; Narbutt, Joanna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2007)
Melkersson-Rosenthal syndrome (MRS) is characterized by cheilitis granulomatosa, congenital plicated tongue and recurrent peripheral facial nerve palsy. Differential diagnosis of MRS includes Quincke’s oedema, allergic and toxic contact facial dermatitis, recurrent viral (Herpes simplex mostly) or bacterial infections as well as neoplasms. We present the case of a 32-year old woman who for 3 years experienced periodically subsiding painless oedema of the face and both lips. Lesions were diagnosed as recurrent Quincke’s oedema and were treated with antihistamine agents and glucocorticoids with a slight improvement. Allergic history, skin prick tests and patch tests were negative. The patient linked every intensification of the symptoms with an outbreak of labial herpes infection. Six years ago, the patient experienced left-sided transient facial and radial nerve palsy. At admission clinical examination showed labial herpes, oedema of upper and lower lip and plicated tongue. Based on the case history and clinical picture MRS was diagnosed and recurrent Herpes simplex infections were considered as an exacerbating factor. The presented case of MRS, incorrectly treated for many years as Quincke’s oedema, demonstrates the necessity of complex management of the symptoms reported by the patient and reflects the diagnostic difficulties of this rare condition.